2021
DOI: 10.1111/ijsw.12489
|View full text |Cite
|
Sign up to set email alerts
|

Same‐sex partnership in the family policies of Japan, Singapore, and Taiwan

Abstract: Discussions about Asian same‐sex partnerships (SSPs) and queer families are relatively few due to their low social visibility and lack of legal recognition. Aiming to explore the relationship between the state and queer families beyond the Western context, I examine the connections between family‐related policies and laws, marriage and family norms, and SSPs in Japan, Singapore, and Taiwan. These three countries encourage marriage and parenthood within marriage, but they have different policies and laws on sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Beyond the Singaporean context, scholars have found that LGBT+ individuals' life experiences in other societies are also significantly shaped by legal, social, and cultural factors surrounding LGBTQ+ rights and marriage (Chung, 2021;Ecker et al, 2019;Sansone, 2019). In the Western context, despite prevailing non-discriminatory laws, scholars found that these laws do not protect same-sex couples (Burke et al, 2022;Cahill & Tobias, 2006).…”
Section: State Policies and Heteronormativitymentioning
confidence: 99%
See 4 more Smart Citations
“…Beyond the Singaporean context, scholars have found that LGBT+ individuals' life experiences in other societies are also significantly shaped by legal, social, and cultural factors surrounding LGBTQ+ rights and marriage (Chung, 2021;Ecker et al, 2019;Sansone, 2019). In the Western context, despite prevailing non-discriminatory laws, scholars found that these laws do not protect same-sex couples (Burke et al, 2022;Cahill & Tobias, 2006).…”
Section: State Policies and Heteronormativitymentioning
confidence: 99%
“…Drawing upon the US context, parallels emerge in the context of Singapore's public housing landscape. In Asian countries such as Taiwan, Japan, and Singapore, marriage is deeply intertwined with family and is often regarded as a precondition for childbirth (Chung, 2021). Consequently, same-sex couples face limited access to family resources and legal rights due to legal restrictions and the lack of marriage recognition (Chung, 2021).…”
Section: State Policies and Heteronormativitymentioning
confidence: 99%
See 3 more Smart Citations